Severe pegfilgrastim-induced bone pain completely alleviated with loratadine: A case report. (August 2015) - Romeo, Cristina; Li, Quan; Copeland, Larry
Febrile neutropenia is an oncologic emergency that can result in serious consequences. Granulocyte colony stimulating factors (G-CSFs) are often used as prophylaxis for febrile neutropenia. Bone pain is the most notorious adverse effect caused by G-CSFs. Specifically, with pegfilgrastim (Neulasta®), the incidence of bone pain is higher in practice than was observed during clinical trials. Traditional analgesics, such as non-steroidal anti-inflammatory drugs (NSAIDs) and opioids, can be ineffective in severe pegfilgrastim-induced bone pain. With the high frequency of this adverse effect, it is clear that health practitioners need additional treatment options for patients who experience severe pegfilgrastim-induced bone pain. The mechanisms of bone pain secondary to G-CSFs are not fully known, but research has shown that histamine release is involved in the inflammatory process. There is scant previous clinical data on antihistamine use in the management of G-CSF-induced pain. We present the first case report in which loratadine prophylaxis completely alleviated NSAID-resistant severe pain secondary to pegfilgrastim. The result showed that loratadine may be a promising option for severe, resistant pegfilgrastim-induced bone pain. Further clinical studies are warranted and ongoing.